Reading as a Device Business: Implications for an eBook Age. - Kositsky, Nina (International Journal of the Book, 2012)
The current shift from the dominance of the medium of the book to the dominance of the medium of the screen is changing our literary landscape: new digital technologies offer us "a new kind of book and new ways to write and read" (Bolter, 1991). As reading migrates from print to digital, it increasingly becomes a device business. While technical considerations dominate the public discourse in regards to what reading hardware to choose (e.g., e-Ink versus color LCD, visual gimmicks like simulated page-flipping, etc.), concerns about the process of reading have been largely absent from the debate. The purpose of this paper is to highlight reading as an immersive and creative experience that fosters a particular kind of imagination, which depends on the reader's ability to "fill words with meaning" (Kress, 2003). The paper emphasizes that interaction with a static text is figurative because the entire responsibility of activity falls on the reader. Digital texts and the various symbol systems they entail, on the other hand, offer a reading experience that is literally interactive (Reinking, 2001). Electronic reading devices vary significantly in terms of the degree of immersion in a textual world they encourage, in terms of the work of imagination they require, and the type of interactivity they imply. The paper argues that these considerations can be used as criteria for selecting a medium that would offer a desirable reading experience.